The Develoment of Reciting al-Quran by Nuraniyah System with Motion Infographic for Primary School Students of Malay Females Foundation for Developing Education. - มูซอ, ซาฮีดะห์; โต๊ะแม, ยามีละห์ (Al-HIKMAH Journal, 2021)
The objectives of this study were1. to develop and find efficiency of Motion Infographics for primary school students at Malay Females Foundation in order to develop education in accordance with criteria 80/80, 2. to develop reading skills for Al-Quran by Nuraniyah System by using Motion Infographic media for primary school students at Malay Females Foundation for developing education and 3. to compare learning achievement of students for reading Al-Quran by Nuraniyah system with motion infographics for primary school students of Malay Females Foundation for developing education and 4. to assess student satisfaction on learning management by using motion infographics for primary school students of Malay Females Foundation for developing education. Target group included primary school students at Malay Females Foundation for developing education in the second semester and academic year 2020 by using specific sampling. Research tools included 1. 8 stories of motion infographics each story per 2 hours 2. Al-Quran reading pre and post skill test for each learning plan, 3. Pre and post achievement test for 40 topics as objective test for 3 choices and 4. student satisfaction survey on motion infographic media. Statistics were percentage, mean, standard deviation and comparing differences of t-test dependent. The results indicated that 1. efficiency of motion infographics was equal to E1/E2 = 86.72/88.25, 2. Al-Quran reading skills of students who received learning management by using motion infographics of post-test were higher ( = 69.37, = 5.17) than pre-test ( = 49.30, = 10.75) , 3. learning achievement of students who received learning management by using motion infographics of post-test was higher ( = 35.30, = 2.31) than pre-test ( = 20.57, = 6.61), and 4. students had satisfaction on studying motion infographics in overview at much level ( = 4.04, = 0.12). Keywords: The Develoment of Reciting al-Quran by Nuraniyah System, Motion Infographic